Early intervention to improve later speech and language trajectories in young autistic children - Lindsay, Clarissa C. (Curtin University, 2010)
The pivotal role of joint attention as a preverbal indicator of childhood autism and as a precursor for later language, play, and social development has been noted by many researchers. Despite the wide and varied literature highlighting the importance of joint attention deficits in young autistic children and calling for intervention approaches, only a small number of intervention studies exist. Few of these studies specifically target joint attention skills. Moreover, the small numbers of studies which directly teach joint attention do not provide sufficient detail to enable replication of the research. Clear objectives and rationales for the treatment are missing and often language is not considered as an outcome variable.The proposed research is an attempt to address this problem, and hence explored the impact of systematically promoting joint attention abilities in verbal autistic preschool children to improve later speech and language trajectories. The intervention sessions were explained by providing information on the general approach during intervention and specific sample tasks. Objectives of the intervention followed developmental trajectories of typically developing children and were clarified by providing rationales. A single subject multiple-baseline design across participants was implemented to evaluate intervention effects on four autistic children. It involved measurements taken from videos of each session of the intervention (coding of joint attention) and outcome variables (coding of language). In addition, there were quantitative measures completed with each child at pre-intervention, post-intervention and follow up stages. These involved an Autism Rating Scale and a battery of language measures. The proposed research had the potential to provide a framework for future research relating to specific intervention programs designed to develop joint attention and language skills in autistic children.